Corneal Endothelial Cell Loss after Phacoemulsification with and without Trypan Blue ? 218 Assisted Staining of Anterior Lens Capsule - Ummarah Rasheed, Arooj Amjad, Muhammad Shaheer (Pakistan Journal of Ophthalmology, 2018)
PURPOSE: To study the mean loss of corneal endothelial cell in patients undergoing cataract surgery with phacoemulsification with and without trypan blue. STUDY DESIGN: Randomized controlled trial PLACE AND DURATION OF STUDY: Institute of Ophthalmology, Mayo Hospital/ King Edward Medical University, Lahore. From 1-1-2016 to 30-5-2017 MATERIAL AND METHODS: 152 patients presenting to the Institute of Ophthalmology were included in study. Patients diagnosed with cataract were selected for surgery. The patients were divided into two groups A and B. Group A patients underwent phacoemulsification with trypan blue aided central curvilinear capsulorhexis while Group B patients underwent phacoemulsification without any aid of trypan blue. Patients with any corneal opacity were excluded from study. Specular microscopy was done on all patients before and three months after surgery. On specular microscopy, corneal endothelial count, hexagonality and coefficient of variation were noted. Specular microscopy and recording of findings was done by researcher. RESULTS: Endothelial cell loss was observed in both the groups but it was more in the Group A (74.3421±0.6332)as compared to the Group B (37.0658±2.6891) (p 0.000). CONCLUSION: Phacoemulsification decreases corneal endothelial cell count both with and without trypan blue. The decrease in corneal endothelial cell count was more when phacoemulsification was done with trypan blue but it did not lead to corneal decompensation. KEY WORDS: Phacoemulsification, Trypan Blue, Corneal Endothelial Cell Count.